ST2 and IL-33 polymorphisms and the development of childhood asthma: a prospective birth cohort study in Finnish children - Teräsjärvi, Johanna T. (John Wiley & Sons, 2025)
The ST2/IL-33 signaling pathway has an important role in the host inflammatory response. Here we aimed to study the association of ST2 and IL-33 polymorphisms with serum soluble (s) ST2 and IL-33 concentrations in healthy Finnish children and, in addition, their association with childhood asthma. In total, 146 children were followed from birth to the age 7 years for the development of asthma. Single-nucleotide polymorphisms (SNPs) in ST2 and IL-33 were determined, and associations of the SNP variants with serum levels of sST2 and IL-33 at age of 13 months and with recurrent wheezing and childhood asthma at 7 years of age were analyzed. Children with ST2 rs1041973 AC/AA genotypes had significantly lower level of serum sST2 (2453 pg/mL; IQR 2265) than those with CC genotype (5437 pg/mL; IQR 2575; p = < 0.0001). Similar difference was also observed with ST2 rs13408661. No differences were observed between subjects with studied IL-33 SNPs. Children who carried genetic variants of ST2 rs1041973 or rs13408661 seemed to have a higher risk of asthma. In contrast, children who carried genetic variants of IL-33 rs12551268 were less often diagnosed with asthma. Even though these SNPs seemed to associate with asthma, the differences were not statistically significant.